Factors influencing perceptions of processed baby foods and feeding practices among Indian mothers: a qualitative investigation - Suruchi Singh (BMC, 2024)
Abstract Objective To explore how professionally qualified, working Indian mothers conceptualize healthy foods in general, perceive processed infant and baby foods available commercially and what feeding practices they actually follow with their children at home. Design Five focus groups with 8-12 participants were conducted around the participants' conceptualization of healthy food, their perceptions about commercially available processed baby and infant foods and their actual feeding practices that they routinely follow with their children. Discussion transcripts were analyzed using an inductive coding approach. Setting India. Participants Fifty-one professionally qualified, working women with at least one child under 5 years of age. Results Participants agreed that fresh food is healthiest. They also had favorable opinions about processed infant and baby foods with regards to healthfulness, hygiene and safety. Healthy foods were largely conceptualized in relation to nutrient claims, ingredients and discernible health outcomes. They use cues, such as health claims, brand, price, package design and others to determine healthfulness of the product. Perception was heavily influenced by these extrinsic cues rather than by participants' own nutrition knowledge. Despite having the knowledge, most participants admitted to using these foods on account of factors such as their own inability to lactate, social pressure, lack of time and convenience. Conclusions Most educated and well off people continue to use these products. While they rue the lack of stringent regulatory measures in India, they feel there is an urgent need to address this huge policy gap by way of legislation and regulation.